Book review: Climate change and life: The complex co-evolution of climate and life on Earth, and beyond, by Gabriel Filippelli, 2022. Elsevier, Amsterdam. 275 pages. Paperback: price $135.00, ISBN 978-0-12-822568-4 - Fu, Li (Geologos, 2023)
Book review: Climate change and life: The complex co-evolution of climate and life on Earth, and beyond, by Gabriel Filippelli, 2022. Elsevier, Amsterdam. 275 pages. Paperback: price $135.00, ISBN 978-0-12-822568-4.